A Place of Opportunity - Joseph N. Cooper; Billy Hawkins (University of Kansas Libraries, 2012)
The purpose of this study was to identify key factors associated with the academic achievement and positive college experiences among Black male student athletes at a Historically Black University (HBU) in the Southeastern United States (U.S.). A concurrent triangulation exploratory design allowed both qualitative and quantitative data to be collected simultaneously and converged during the analysis phase (Creswell, 2009). Participants in this study included current Black male student athletes who participated in football and men's basketball at a HBU in the Southeastern U.S. Using aspects of the grounded theoretical approach for analysis (Glaser & Strauss, 1967), the following emergent themes were identified: "You Got a Chance," "An Opportunity," "Not Just a Number," "It's Hard, But It's Not Impossible" and "As An Athlete It Makes Your Social Life a Little Easier." Implications for policy and practice are discussed.